The RDA primer : - Hart, Amy (Linworth, 2010)
This book traces the development of RDA, explaining why it was needed and how it was developed. The basics of the conceptual models for RDA are covered, showcasing the origins of the structure and vocabulary of RDA. It then compares AACR2 to RDA and looks at specific changes in the cataloging code. The author also addresses how this development may enable library data to be housed on the Semantic Web and provides practical advice that librarians and catalogers can act upon now to prepare for RDA